Borrowing Costs and the Demand for Equity over the Life Cycle - Davis, Steven J; Kubler, Felix; Willen, Paul (The Review of Economics and Statistics, 2006)
We construct a life cycle model that delivers realistic behavior for both equity holdings and borrowing. The key model ingredient is a wedge between the cost of borrowing and the risk-free investment return. Borrowing can either raise or lower equity demand, depending on the cost of borrowing. A borrowing rate equal to the expected return on equity—which we show roughly matches the data—minimizes the demand for equity. Alternative models with no borrowing or limited borrowing at the risk-free rate cannot simultaneously fit empirical evidence on borrowing and equity holdings.